Strategic Human Resource Management and Employee Performance in Islamic Banking: The Mediating Roles of Work Motivation and Job Satisfaction - Ventje Jeffry Kuhuparuw; Sherly Ferdinandus; Melyani Melyani; Jihn-Chang Jehng (MIX: JURNAL ILMIAH MANAJEMEN, 2026)
Purpose: This study examines the effect of financial compensation as a strategic human resource management practice on employee performance in Islamic banking. It also investigates the mediating roles of work motivation and job satisfaction in explaining this relationship.Methodology: A quantitative research design was employed using survey data collected from employees in the Islamic banking sector. The proposed relationships among financial compensation, work motivation, job satisfaction, and employee performance were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM).Findings: Financial compensation has significant positive effects on work motivation (β = 0.62; p < 0.001) and job satisfaction (β = 0.58; p < 0.001). Work motivation (β = 0.41; p < 0.001) and job satisfaction (β = 0.37; p < 0.001) also significantly improve employee performance. These findings demonstrate that financial compensation enhances employee performance indirectly by strengthening employees’ motivation and satisfaction, confirming the mediating roles of both variables.Conclusion: Competitive and equitable financial compensation constitutes a strategic human resource practice that can enhance employee motivation, job satisfaction, and performance in Islamic banking. Human resource managers should therefore develop transparent, performance-oriented, and Sharia-aligned compensation systems to retain employees and support sustainable organizational performance.